Influence of atmospheric pressure plasma treatment on mechanical proprieties of enamel and sealant bond strength. Issue 5 (20th September 2014) - Teixeira, Hellen S.; Coelho, Paulo G.; Duarte, Simone; Janal, Malvin N.; Silva, Nelson; Thompson, Van P.
Abstract Objectives To define the effect of APP treatments on the mechanical properties of enamel and on its ability to promote sealant bonding to unetched enamel. Methods Human molar teeth were sectioned exposing flat enamel regions at the buccal and lingual surfaces. The specimens were divided into two substrate groups (etched and unetched) and distributed over three surface treatments (i) 5 slm Argon APP treatment, NaOH surface treatment, and (iii) compressed air application (control). The Enamel surfaces were characterized by SEM, IFM, and Goniometer instruments. For the mechanical tests nanoindentation and microshear bond strength were employed. Initial data evaluation comprised normality verification (SPS S software) and variance checking and the appropriated statistical analysis model employed. For all statistical inferences, significance was set at 0.05. Results SE was significantly higher for the etched and unetched group treated with Plasma relative to the NaOH and control groups. Nanoindentation testing determined that Rank hardness was significantly higher in the control and Plasma group relative to NaOH for the etched group. Rank Elastic Modulus was significantly higher on Control groups relative to NaOH and Plasma groups for the etched substrate. No difference was detected between treatments for the unetched group. For the µSBS test, we observed that APP treatment on etched and unetched enamel increased bonds significantly (p < 0.001). Conclusions This study demonstrated that APP increased SE, surface wettability and bond strength between enamel and sealants potentially serving as a substitute for conventional acid etching procedures or as an adjuvant for self‐etch sealants. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1082–1091, 2015.